World Class Quality Using Design of Experiments to Make It Happen - Bhote, Keki R.; Bhote, Adi K. (Amacom, 2000)
The book that crowned the quality revolution (with over 100,000 copies sold since 1991) is poised to make it happen all over again. This new and expanded edition of the widely influential World Class Quality not only provides more techniques and case studies, but also extends them into new areas (such as the service sector) and shows how to use them in a wider variety of applications. A new coaching emphasis makes it easy for managers to make these tools available at all levels of a company and even to customers and suppliers. The book also offers: A practical way to secure top management commitment and make "Design of Experiments" a way of life at any company A new reliability technique that simulates field failures at the design stage so they can be prevented before production A new chapter summarizing related quality management and control techniques, making this an essential book for managers concerned with quality.